ANALISIS MANAJEMEN KURIKULUM PENDIDIKAN KEPESANTRENAN DI PONDOK PESANTREN TAHFIDZUL QUR’AN AZIZIYYAH TANGERANG - Saabirah Sayidatun Nisa; Adellia Azzizah; Ainun Ardilah; Lia Nur Afriyanti (STKIP Pesisir Selatan, 2025)
This method to find out the results of the study shows that the purpose of this study is to see how the management of the Islamic boarding school education curriculum is carried out at the Tahfidzul Qur'an Aziziyyah Islamic Boarding School in Tangerang. To produce students who excel spiritually, intellectually, and in character. The Islamic boarding school curriculum not only functions as an academic standard but also helps students grow in morals, discipline, and social responsibility. This study was conducted with a qualitative approach and case studies. Islamic boarding school leaders, curriculum managers, ustadz, and students were involved in data collection through observation, interviews, and documentation studies. The Miles and Huberman model method was used to conduct data analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the Tahfidzul Qur'an Aziziyyah Islamic Boarding School in Tangerang combines the Islamic boarding school curriculum, the Ministry of Religion curriculum, and contemporary education models in a planned and integrated manner. The curriculum is adapted to changing times while maintaining the traditional values ​​of the Islamic boarding school, emphasizing the balance between mastery of religious knowledge, language skills, and the use of technology as well as the formation of the character of students.